Prevalence of interfering antibodies in dogs and cats evaluated using a species‐independent assay. (14th June 2018) - Bergman, Daniel; Larsson, Anders; Hansson‐Hamlin, Helene; Svensson, Anna; Holst, Bodil Ström
Abstract : Background: Interfering antibodies in human serum and plasma are known to react with mammalian antibodies in immunoassays and cause false‐positive test results. Although this phenomenon was recently shown in companion animals, knowledge regarding immunoassay interference in veterinary medicine is very limited. Objectives: The aims of this study were to set up a species‐independent immunoassay procedure to detect interference in serum samples, to screen for interference in a cross‐section of canine and feline patient samples from an animal hospital, and to determine if the detected interference could be neutralized using an immunoassay based on nonmammalian reagents. Methods: A 2‐site sandwich‐type interference assay was set up using commercially available mouse reagents. A total of 369 serum samples from 320 dogs and 263 samples from 218 cats were analyzed using the interference assay. Multiple samples were submitted from 36 dogs and 39 cats. Nineteen samples identified as interference‐positive were analyzed in an assay using chicken antibodies. Results: Interference was detected in samples from 28 dogs (9%) and 10 cats (5%) screened with the interference assay. Except for 1 cat, consistent results were obtained for all 75 dogs and cats that submitted more than 1 sample. The interference was eliminated when analyzed in the chicken‐based assay ( P < .001). Conclusions: Substances with reactivity toward mouse IgG can be detected in serum samples from dog and cat patients using a 2‐site interference assay. The detected substances are most likely interfering antibodies, possibly originating from immunization with other mammalian species.